Effects of biologic therapy on novel indices of lung inhomogeneity in patients with severe type-2 high asthma - Nayia Petousi; Nick P Talbot; Ian Pavord; Peter A Robbins; Nicholas M J Smith; Graham Richmond; Asma Alamoudi; Lorenzo Petralia; Haopeng Xu; Dominic Sandhu; Grant AD Ritchie (BMJ Open Respiratory Research)
Introduction/Aim Lung inhomogeneity measures obtained using computed cardiopulmonography (CCP) are sensitive to small-airways disease. Here, we assessed changes in lung inhomogeneity in patients with type-2 high asthma treated with biological therapy and explored the relationship between inhomogeneity measures and conventional asthma disease markers.Methods This was an observational study of 91 severe type-2 high asthma patients recruited from a tertiary asthma clinic, of whom 67 subsequently started anti-IL5 or anti-IL5R biologics. Patients were evaluated at baseline and, 54 of those commencing biologics, at their fourth injection with either mepolizumab or benralizumab. Assessments included prebronchodilator and postbronchodilator CCP and spirometry, and measurements of blood eosinophil count (BEC), fractional exhaled nitric oxide and Asthma-Symptom Questionnaire (ACQ-5).Results Bronchodilation significantly reduced σlnCl, a novel CCP-derived ventilation inhomogeneity index, (ΔσlnCl −0.08, 95% CI (−0.10 to –0.05), p<0.001). Baseline σlnCl, but not forced expiratory volume in 1 s (FEV1) % predicted, was significantly associated with BEC (linear mixed-effects (LME) regression coefficient for BEC 0.18, 95% CI (0.04, 0.32), p=0.01). Following biologics, improvements in σlnCl were significantly dependent on BEC (LME regression coefficient +0.19, 95% CI (0.11, 0.27), p<0.001) whereas improvements in FEV1 % predicted related to both BEC and ACQ-5 responses (LME coefficients: BEC −10.8 % pred, 95% CI (−16.1,–5.5); ACQ-5 –3.5 % pred, 95% CI (−5.1 to –1.9), p<0.001). Following biologics, the change in σlnCl followed a bimodal distribution that dichotomised patients into σlnCl-Responders and σlnCl-Non-Responders. Responders, unlike Non-Responders, experienced significant improvements in symptoms and FEV1 % predicted (Δ pre-BD FEV115±15% pred, p<0.001) and included a higher proportion of patients in clinical remission at 1 year.Conclusion σlnCl is strongly associated with systemic eosinophilic inflammation in severe type-2 high asthma. An early σlnCl response following anti-IL5 biologics identifies patients more likely to experience improvements in symptoms and lung function when systemic eosinophils are depleted. σlnCl may provide a sensitive route for tracking inflammation involving the small airways.